Proximate Composition, Mineral and Phytochemical Characterization of Mangifera Indica Leaves - Remi Victor-Osanyinlusi; Eneji Ademoh Sanni (Biology, Medicine, & Natural Product Chemistry, 2026)
This study evaluated the proximate composition, mineral content, and phytochemical constituents of Mangifera indica leaves to assess its nutritional and medicinal potential. Fresh leaves were collected, processed into powder, and subjected to standard analytical procedures. Proximate analysis revealed moisture (11.06%), ash (8.01%), crude fat (3.09%), crude fibre (7.05%), crude protein (17.09%), and carbohydrate (53.70%) contents. Mineral analysis confirmed the presence of essential elements, while qualitative phytochemical screening indicated the presence of bioactive compounds such as flavonoids, tannins, and phenolic compounds. The relatively low moisture content suggests good storage stability, while the appreciable protein, fibre, and ash values indicate nutritional and functional significance. The presence of phytochemicals further supports its traditional use in the management of metabolic and infectious diseases. In conclusion, Mangifera indica leaf possesses significant nutritional and therapeutic properties, highlighting its potential application in functional foods, nutraceuticals, and traditional medicine.